Hipertiroidisme: Sebuah Studi Laporan Kasus - Saraswati, Niluh Ayu Sri; Salutondok, Welly (Wellness And Healthy Magazine, 2022)
Introduction: Hyperthyroidism, an excessive concentration of thyroid hormones in tissue, is one of the major thyroid diseases in Indonesia. In 2007, the prevalence of hyperthyroidism in Indonesia is higher in women (14.7%) than men (12.8%) and stands at 6.9%, with TSH cut-off level less than 0.55 µIU/mL. Clinical signs and symptoms may vary according to the patient’s age, duration of illness, the magnitude of hormone excess, and presence of comorbid conditions. Methods: We present a case of diagnosis and treatment of hyperthyroidism in our health care unit. Complimentary databases were collected from PubMed and Google Scholar. Results: A 33 years old male patient presented with fatigue, palpitation, weight loss, a month before being admitted to the hospital. We suspected the patient is having a hyperthyroidism condition and used Wayne’s index to evaluate the score. More information such as the preference for cold, an increase of appetite, and hyperhydration was dug. The total score is 20 which signaling hyperthyroidism. The patient undergoes other examinations such as ECG (sinus tachycardia, rate 104 bpm), thyroid function (TSH 0.0039 µIU/mL, FT4 3.26 ng/dL), liver function (OT 31 U/L, PT 49 U/L), and electrolyte (Na 142 mEq/L, K 3.67 mEq/L). The patient has been treated with PTU 100 mg (3 times a day), propranolol 10 mg (2 times a day), and Curcuma 1 tablet (3 times a day). Discussion: Diagnosing hyperthyroidism begins with digging clinical information, counting Wayne’s index, and checking specific laboratory examinations. Treatment may vary according to symptoms and laboratory results.  Abstrak Pendahuluan: Hipertiroidisme, sebuah kondisi peningkatan hormon tiroid pada tubuh, merupakan salah satu masalah tiroid terbesar di Indonesia. Pada tahun 2007, prevalensi hipertiroidisme di Indonesia pada wanita (14.7%) lebih besar dibanding pria (12.8%), dan berada pada angka 6.9%, dengan nilai TSH kurang dari 0.55 µIU/mL. Tanda dan gejala klinis dapat bervariasi sesuai dengan usia pasien, durasi sakit, kadar hormon, dan kondisi komorbid. Metode: Laporan kasus ini akan memaparkan diagnosis dan terapi pada sebuah kasus hipertiroidisme yang ditemukan pada fasilitas layanan kesehatan tempat kami bekerja. Data penunjang didapatkan dari PubMed dan Google Cendekia. Hasil: Pasien merupakan seorang pria berusia 33 tahun dengan keluhan mudah lelah, berdebar, dan penurunan berat badan dalam 1 bulan terakhir. Kami mencurigai pasien dengan hipertiroidisme dan menggunakan indeks Wayne untuk mengevaluasi skor. Keluhan lain yang dialami oleh pasien yakni tidak tahan panas, peningkatan nafsu makan, dan mudah berkeringat. Skor total yang didapatkan ialah 20 yang menandakan pasien mengalami kondisi hipertiroidsme. Dilakukan pemeriksaan penunjang lain pada pasien berupa EKG (sinus takikardia, Nadi 104x/menit), fungsi tiroid (TSH 0.0039 µIU/mL, FT4 3.26 ng/dL), fungsi liver (OT 31 U/L, PT 49 U/L), dan elektrolit (Na 142 mEq/L, K 3.67 mEq/L). Pasien diterapi dengan PTU 3 x 100mg, propranolol 2 x 10mg, dan curcuma 3 x 1 tablet. Simpulan: Mendiagnosis hipertirodisme dimulai dengan penggalian informasi keluhan pasien, penghitungan indeks Wayna, dan pemeriksaan penunjang spesifik lainnya. Terapi dapat berbeda sesuai dengan kondisi dan hasil pemeriksaan laboratoris pasien.